Aerodynamic Optimization of a Wind Turbine Blade Designed for Egypt's Saharan Environment Using a Genetic Algorithm - Khaled Yassin; Aya Diab; Zakaria Ghoneim (Renewable Energy and Sustainable Development)
This work aims to optimize the aerodynamic parameters (airfoil chord lengths and twist angles smoothed using Bezier curves) of the NREL 5MW wind turbine and a wind turbine designed for site-specific wind conditions to increase the wind turbine's annual energy production (AEP) under this site conditions. This optimization process is carried out using a Genetic Algorithm (GA) developed in MATLAB and coupled with NREL's FAST Modularization Framework. The results shows that after optimizing the NREL 5MW wind turbine design, the AEP was improved by 5.9% of the baseline design AEP while a site-specific designed wind turbine using Schmitz equations shows 1.2% improvement in AEP. These results shows that optimization of wind turbine blade aerodynamic parameters for site-specific wind conditions leads to improvement in AEP and hence decreasing cost of energy generated by wind turbines.